Solitary fibrous tumors: Clinical and imaging features from head to toe. Issue 146 (January 2022) - Badawy, Mohamed; Nada, Ayman; Crim, Julia; Kabeel, Khalid; Layfield, Lester; Shaaban, Akram; Elsayes, Khaled M.; Gaballah, Ayman H.
Highlights: Solitary fibrous tumors (SFTs) are well defined hypervascular spindle cell neoplasms, occurring in a wide variety of locations. SFTs may be locally aggressive or may even metastasize. Benign and malignant SFTs may show uniform or heterogeneous contrast enhancement on CT and MRI. The characteristic histopathologic findings of SFTs may overlap with other neoplasms. However, the molecular and immunohistochemical findings of SFTs are pathognomonic. Abstract: Solitary fibrous tumors (SFTs) are rare fibroblastic mesenchymal tumors that are usually benign with variable malignant potential. They can develop in any organ due to their spindle cell origin. The exact etiology of solitary fibrous tumors is unknown. The majority of SFTs are benign with 10–30% of them exhibiting aggressive and malignant features. The aggressiveness of this type of tumor is not associated with its histological features, which makes surgical resection the treatment of choice. We will review the clinical and radiological features and possible differential diagnoses of SFTs according to their anatomical sites following the World Health Organization 2020 classification.